Beyond Spiritual Authority: Revitalising Charismatic Leadership for Economic Independence in Indonesian Pesantrens - Bachrul Ulum; Halili Halili; Wahyu Fajar Filastin; Silfin Aisyah (Al-Qalam Institute, 2025)
This study aims to analyze the strategy and impact of revitalizing the Kyais ’ role in achieving sustainable economic Independence in pesantren. In the context of emerging economies, pesantrens possess significant social capital but remain vulnerable due to their financial dependence on external funding. This condition underscores the need to transform traditional spiritual leadership into a more professional, entrepreneurial model to support institutional sustainability. This research employs a qualitative approach with an instrumental case study design at the Islamic Boarding School, using purposive sampling. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using an interactive model with triangulation to ensure validity. The findings reveal that the Kyai acts as the central architect of economic governance, integrating moral authority with strategic decision-making. Leadership revitalization is implemented through professional delegation, resource mapping, and vocational integration. This process produces a hybrid governance model combining centralized control and decentralized management.Furthermore, pesantren successfully transitioned into a production-based economic system. This transformation strengthens financial autonomy, student entrepreneurship, and community empowerment. The study contributes theoretically by proposing a charismatic–entrepreneurial leadership model and practically by offering a strategic framework for institutional Independence.